PERBEDAAN RETURN DAN RISIKO SAHAM PERUSAHAAN YANG TERCATAT PADA INDEKS KOMPAS 100 TAHUN 2011-2015 SETELAH MELAKUKAN AKUISISI SAHAM - Ryan Farandy (Parsimonia - Jurnal Ekonomi dan Bisnis, 2015)
Business environment these day was very quickly changes, that condition make firm for compulsory service always deveop strategies for which would survive and won in business competition, one of the method is acquisition. This research is to study of the acquisition of company shares that can affect return (rate of return) of shares and share risk. The object of research is public companies listed on the Index Kompas 100 in 2011-2015. The sample of this research consist of 12 companies that have undertaken acquisitions of shares above 50% in the given period. Financial datas in this research acquired from financial reportment for the period of 2011-2015. This data obtained from www.idx.co.id, www.duniainvestasi.com, and yahoo finance. Stock returns are calculated on the percentage change in the stock price closing the year end. Factors which cause diverification stock returns and stock risk in this study is the acquisition of shares made by the company. Data was analyzed and observed against the average stock return by using Paired Sample T- Test to compare differences in risk and return stocks 10 days before and 10 days after the acquisition of shares. The results showed that the acquisition of shares does not provide a significant difference to the return and risk stock